2023
DOI: 10.14309/crj.0000000000001168
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Gastric and Colonic Metastasis of Breast Cancer

Inês Botto,
Rafael Moiteiro Cruz,
Carlos Noronha Ferreira
et al.

Abstract: Although breast cancer (BC) is the most common malignancy in women, metastasization to the gastrointestinal tract is rare. We present a 59-year-old woman with simultaneous gastric and colonic metastasis of invasive lobular breast carcinoma. She had been diagnosed with BC and underwent surgery and systemic therapy. Two years later, an increase in tumor markers motivated investigation, including upper and lower gastrointestinal endoscopy, which identified gastric ulcers and mucosal irregularity in the cecum. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Conversely, GI metastases are uncommon, and previous studies have reported that the occurrence of gastric and colonic metastases is as low as 3% and 5%, respectively [ 7 ]. Moreover, simultaneous gastric and colonic metastasis is exceptionally rare, with only eight documented cases, including the case presented in our study [ 8 ]. Breast cancer, especially the luminal type, demonstrates a persistent tendency to recur, often spanning a prolonged period that sometimes exceeds 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, GI metastases are uncommon, and previous studies have reported that the occurrence of gastric and colonic metastases is as low as 3% and 5%, respectively [ 7 ]. Moreover, simultaneous gastric and colonic metastasis is exceptionally rare, with only eight documented cases, including the case presented in our study [ 8 ]. Breast cancer, especially the luminal type, demonstrates a persistent tendency to recur, often spanning a prolonged period that sometimes exceeds 20 years.…”
Section: Discussionmentioning
confidence: 99%